Peningkatan Tebal Lapis Perkerasan Kaku pada Jalan Yos Sudarso Kumbe dengan Metode AASHTO - D.S. Nababan; Z. Abidina; C. Utary (Civil Engineering Department, Tadulako University, 2023)
Yos Sudarso Road is a connecting road heavily traveled by heavy vehicles. The number of heavy vehicles that often pass through this road is one of the supporting factors for the damage to the road, in addition to the absence of maintenance and improvement carried out, resulting in a decrease in the level of serviceability of the road. This condition is the main objective of this research, namely to determine the design of increasing the thickness of the rigid pavement layer on Jalan Yos Sudarso Kumbe. The method used in this improvement is the American Association Of State Highway And Transporting official 1993. The research conducted on Yos Sudarso Kumbe road includes collecting CBR data using DCP tools, surveying traffic volume to find the LHR value, then observing how long the puddle of rainwater on the road surface will disappear to determine the drainage quality. From the results of the analysis and calculations carried out using the 1993 AASHTO method with 15% CBR, the thickness of the pavement layer is 135 mm (5.2 inches) because the thickness of the pavement layer does not meet the minimum standard of rigid pavement thickness with low traffic volume. The minimum standard of rigid pavement thickness with low traffic volume is 150 mm (6 inches), with D10 mm reinforcement and 30 cm spacing between support, D19 mm dowel, 45 cm length, 30 cm spacing between bars, and D16 mm tie bars, 70 cm length, 75 cm spacing between bars.